2007
DOI: 10.2478/v10007-007-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of germanium L-cysteine α-tocopherol complex as stimulator of some antioxidant defense systems in gamma-irradiated rats

Abstract: This study was conducted to evaluate the potency of the newly prepared germanium L-cysteine a-tocopherol complex [germanium dichloro tetrakis (L-cysteinyl-a-tocopherol amide) dichloride] as a protective agent against g-irradiation-induced free radicals production and liver toxicity. Male Swiss albino rats were injected intraperitoneally with the germanium complex in a concentration of 75 mg kg -1 body mass per dose, for 6 successive doses, last dose administered twenty minutes pre-exposure to a single dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
1
11
0
2
Order By: Relevance
“…In the present study, there was a decrease in contents of total proteins in serum of rats irradiated with gamma radiation, indicating liver injury [1,43]. These results are in accordance with other studies using high-energy radiation from cobalt source [44].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, there was a decrease in contents of total proteins in serum of rats irradiated with gamma radiation, indicating liver injury [1,43]. These results are in accordance with other studies using high-energy radiation from cobalt source [44].…”
Section: Discussionsupporting
confidence: 93%
“…A study has reported that high amounts of phycocyanobilin present in Spirulina inhibit the activity of NADPH oxidase ( 34 ) . Moreover, various studies have suggested that germanium compounds may have protective effects against liver injury, as well as antioxidant effects ( 17 , 19 , 20 ) . Thus, GeSP is believed to exert synergistic effects of both Spirulina and germanium.…”
Section: Resultsmentioning
confidence: 99%
“…Germanium is present in all living plant and animal matter in micro-trace quantities. Although inorganic germanium (germanium dioxide) has been shown to have toxic effects ( 14 ) , organic germanium has therapeutic attributes including immune enhancement ( 15 ) and antioxidative effects ( 16 , 17 ) . Organic germanium is well known to be effective in protecting against liver injury in mice through reducing the production of interferon-γ (IFN-γ) or TNF-α ( 18 , 19 ) .…”
mentioning
confidence: 99%
“…Они могут присутствовать в клетке в следовых количествах, однако их синтез может быть активирован различными веществами, как непосредственно субстратами, так и синтетическими веществами, ионами металлов и их комплексными соединениями. Среди последних перспективными и в то же время наименее изученными являются координационные соединения активных металлов, в частности германия, с биолигандами [10][11][12]. Уникальные комплексообразующие свойства германия находят применение в различных областях медицины и фармакологии, в том числе и благодаря способности влиять на свойства протеина путем изменения его конформации [12,13].…”
Section: высокий биотехнологический потенциал морских микроорганизмовunclassified
“…В некоторых случаях невысокую исходную активность микробных культур удается индуцировать не только с помощью оптимизации углеродного и азотного питания, а также при использовании химических индукторов. В роли последних, в частности, могут выступать металлы и их координационные комплексы с биолигандами [10,12]. Координационные соединения металлов уже показывали свою эффективность в качестве индукторов синтеза и активности некоторых ферментов [11,20].…”
Section: рис 1 α-L-рамнозидазная активность исследованных штаммов Bunclassified